(untitled) (Scientific journal of the Fergana State University, 2024)
This article examines the practical state of the development and promotion of a healthy lifestyle among students of higher educational institutions and, thus, the functions of physical recovery. A healthy lifestyle is the process of becoming a fully developed personality capable of active work, a life without deviations in creativity, easy tolerance of strong physical and mental loads, extremely dangerous and harmful influencing factors. The development of mental, physical and physiological qualities in students and the maintenance of social activity in an environment of a certain level of working capacity and maximum life expectancy, as well as the essence, goals, objectives of maintaining a healthy lifestyle and the relevance and significance of the functions of a healthy lifestyle of students in physical culture and sports are scientifically substantiated.